Adsorption Removal of Phosphorus from Aqueous Solution by Heat-Activated Alum Sludge - Tie, Jingxi; Chen, Dong; Wan, Yunjie; Yan, Cheng; Zhang, Xiwang (Asian Journal of Chemistry, 2013)
Eutrophication caused by phosphorus is one of the major water pollution problems. In this study, the waste material, alum sludge, was utilized as a phosphorus adsorbent. A facile method of thermal treatment was developed to improve the adsorption capacity of alum sludge. The prepared alum sludge adsorbent was characterized by XRD, XRF and FTIR techniques to analyze its crystal phases and surface properties. The heat treatment had significant impact on the physico-chemical properties of the alum sludge adsorbent, which further influenced its adsorption performance. The optimal heat treatment was 300 ºC. The phosphorus adsorption onto the alum sludge sorbent fitted to Freundlich isotherm very well and the adsorption kinetics followed the pseudo-second-order rate equation. The solution temperature and pH both had apparent influence on alum sludge adsorption capacity. Higher solution temperature and lower pH were favorable for phosphorus adsorption. Thermodynamic parameters showed that the phosphorus adsorption onto alum sludge was spontaneous and endothermic.